Madrasah Head Leadership Strategy: Research Madrasah’s Implementation At State Islamic Junior High School of 2 Sukoharjo - Masruri Masruri; Mudhofir Mudhofir; Yusup Rohmadi; Arief Hendra Kurniawan (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This study aims to analyze the strategy and leadership style of madrasah principals at MTsN 2 Sukoharjo and analyze the implementation of research madrasahs at MTsN 2 Sukoharjo. The problems raised include a) how at a glance about MTsN 2 Sukoharjo in the Research Madrasa Pioneer; b) what is the strategy and leadership style of the madrasah principal at MTsN 2 Sukoharjo; c) how is the implementation of research madrasas at MTsN 2 Sukoharjo; and d) what are the supporters and obstacles for madrasah principals in implementing research madrasas at MTsN 2 Sukoharjo. This research uses a qualitative approach with a qualitative-descriptive type of research. The data obtained came from primary data through a brief online interview with the principal of MTsN 2 Sukoharjo and secondary data through literature review analysis by reading & analyzing literature from various sources such as journals, articles, books, etc. The results of this study indicate that the implementation of research madrasas at MTsN 2 Sukoharjo in reality has not been fully supported by adequate educators. The principal's leadership strategy in supporting research madrasas at MTsN 2 Sukoharjo is carried out through fostering educator performance, supervising educator performance, coaching and affirming educator discipline, and providing motivation. The head of the madrasa at MTsN 2 Sukoharjo uses a leadership strategy with a democratic style, where the head of the madrasa approaches himself with educators, staff, and students.